Lettere scientifiche e non solo tra un premio Nobel e un giovane scienziato Carteggio tra Giulio Natta e Enzo Ferroni dal 1954 al 1968 - Colli, Laura (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2020)
The book presents the correspondence, from the 1950s to the end of the following decade, between the Nobel Prize laureate, Giulio Natta, and a young Enzo Ferroni, who will be then one of the founders of "chemistry applied to restoration". Almost sixty years later, this research has made it possible to recover the memory of Ferroni as an avant-garde scientist also in the field of macromolecules and the possibility offered to him by Natta of a prestigious role as a researcher at his institute in Milan. The archives, even the scientific ones, can reserve surprises of this kind: they are prolific in technical data but also reveal traces of humanity. The volume also includes the joint publication of the two chemists and seven articles by Ferroni presented by Natta at the Accademia dei Lincei.